2018
DOI: 10.24071/llt.v21i2.1259
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Technology in English as a Foreign Language Learning Outside the Classroom: an Insight Into Learner Autonomy

Abstract: This research was conducted to examine Indonesian students' experiences in using technology in learning English outside the classroom with regards to learner autonomy as an important capacity for students learning success. The subjects of the study were students of a private Senior High School in South Tangerang. As for the methodology, this research applied quantitative and qualitative design. Quantitative elements include questionnaires as the data collecting method, while qualitative elements used semi stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 2 publications
1
5
0
Order By: Relevance
“…According to the theory of FLA sources in this study, improving motivation can mitigate students' FLA. The finding is in line with Warni, Aziz and Febriawan' s (2018) research, which indicated that using technology to learn English in the outside classroom can improve students' motivation and self-confidence better than the in-class form, which debilitates their FLA.…”
Section: Discussionsupporting
confidence: 87%
“…According to the theory of FLA sources in this study, improving motivation can mitigate students' FLA. The finding is in line with Warni, Aziz and Febriawan' s (2018) research, which indicated that using technology to learn English in the outside classroom can improve students' motivation and self-confidence better than the in-class form, which debilitates their FLA.…”
Section: Discussionsupporting
confidence: 87%
“…The analysis finds that learning English outside the classroom using technology develops learner autonomy such as learning motivation, metacognitive awareness, self-confidence, and social skills. By these results, Warni et al (2018) conclude that using various information and communication technology is suggested to boost learner autonomy.…”
Section: Introductionmentioning
confidence: 70%
“…In "The Use of Technology in English as a Foreign Language Learning Outside the Classroom: An Insight into Learner Autonomy", Warni et al (2018) implement quantitative design through questionnaires and qualitative design through a semi-structured interview to investigate the learners' autonomy supported by the use of technology in learning English outside the classroom. Students of a private Senior High School are involved during the questionnaires and five of them are selected purposely to be interviewed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the reason above, high motivation is needed for kids to learn English. Using technology as the teaching media mainly in teaching young learners will provide an opportunity for them to be focused, willing to study by themselves and collaborate with their peers (Warni et al, 2018). A media to learn and teach could be anything depending on teachers' capability to liven up the class and their creativity to make kids' motivation to learn English stay high.…”
Section: Introductionmentioning
confidence: 99%